Deconstruction of the wife figure in the Ie system in the anime Tadaima, Okaeri - Putri, Rizqi Amelia; Puspitasari, Diana; Widodo, Heri (Universitas Dian Nuswantoro, 2025)
The development of Japanese popular culture has given rise to various representations of non-traditional families, one of which is through the omegaverse subgenre in boys' love works. The anime Tadaima, Okaeri explicitly presents the omegaverse family through the character of Fujiyoshi Masaki, an omega man who plays the role of wife in the family. This study aims to analyze the deconstruction of the wife figure in the Japanese ie system using Derrida's perspective. The study uses content analysis of 12 episodes of Tadaima, Okaeri. The analysis focuses on the two main duties of the wife in the ie system, namely kaji (domestic work) and ikuji (childcare). The results show that Masaki consistently carries out domestic and caregiving activities traditionally attributed to women. This reversal disrupts binary oppositions such as male-female, public-domestic, dominant-submissive, which have been considered stable in the ie structure. Through Derrida's concept of hierarchy reversal and supplement, this anime shows that the role of wife is not a natural characteristic of women, but rather an interchangeable socio-cultural construct. However, Masaki's presence also further reinforces the patriarchal system that what is appropriate and suitable in the domestic sphere is the status of a wife.